Incorporating indigenous knowledge in the teaching of isiXhosa to pharmacy students at Rhodes University - Mapi, Thandeka Priscilla (Rhodes University, Faculty of Humanities, School of Languages, 2009)
Traditional healing is one of the most trusted methods of healing in South Africa, especially in rural areas, where health-care infrastructure is inadequate. People have depended on this method of healing since time immemorial. That belief has been strengthened by the fact that this method keeps people in touch with their ancestors. Traditional healers are trusted and believed to be the link between people and their ancestors. The Dwesa community is amongst the areas that still have strong belief in traditional healing. Traditional healers have a variety of methods of healing that they use, these methods have been trusted for people of all age groups. These methods are ukugabha, ukufutha and ukucima. Traditional healers prescribe them for both major and minor illnesses. They are believed to play a role in cleansing people from inside and outside. These methods together with other methods that are used in traditional healing are being explored in this study. This exploration is based on the fact that this information will be integrated into the teaching of isiXhosa to Pharmacy students at Rhodes University. This is an initiative to create awareness amongst health-care practitioners about traditional healing methods, so that they can caution and advise their patients about medicine taking behaviours, also to make them approach the subject in a sensitive manner. An isiXhosa course has been taught to Pharmacy students, as a pilot in 2007 and as an elective in 2008 onwards. This course deals with cultural issues in a broad manner, the issue of traditional healing specifically, and these methods of healing are outlined in the course, such that students have an understanding first of what a traditional healer is and their role in providing health-care services.
Keywords: Rhodes University -- Academic Development Programme; Healers -- South Africa; Traditional medicine -- South Africa; Xhosa language -- Study and teaching -- South Africa; Pharmacy -- Study and teaching -- South Africa; Ethnoscience -- South Africa -- Eastern Cape